Novel Methods for Inhibiting Amyloidogenesis in the Presence of Peptides to Block Hydrophobic Interactions - Masatoshi, Saiki; Ikumi, Shibatate (Journal of Peptides, 2024)
Amyloid fibrils, which are caused by abnormal conformation and the mis-assembly of proteins, are responsible for several conformational diseases, including prion diseases. To develop methods to prevent amyloid formation, blocking peptides with hydrophilic substitutions covering the stem forming regions of barnase 1-24 were prepared and examined for their ability to block amyloid-forming fragments—prion, Amyloid β, Pmel 17—. When these fragments were mixed with the synthetic blocking peptides, the result was a decline in the intensity of fluorescence, suggesting that amyloid formation was inhibited. Therefore, amyloidogenesis appears to be specifically inhibited by disrupting the hydrophobic interactions between core amyloid regions.
Keywords: Alzheimer’s disease; Amyloid fibrils; Pmel17; thioflavin T